Assessing the differential treatment of males and females in the criminal justice process: A critical analysis. - Massicotte, Jodi-Anne. (University of Ottawa (Canada), 1997)
This study focuses on the assessment of differential treatment within the criminal justice system and begins with an examination of the law. Although law has a specific claim to neutrality and objectivity, it was created by males in the interests of males. The laws enacted by legislators set the tone for the inferior regard of women and essentialized and sexualized typifications of women were thus reflected in law. The 1960's saw feminists beginning to challenge and critique the law. Feminist legal theorists found that stereotypes about the roles of women resulted in their differential treatment within the legal system in a number of ways. The next section of the thesis undertakes a review of the empirical studies of the administration of differential justice for males and females. The next section of the thesis explores the idea that laws and penal practices have been constructed in a biased fashion. It examines the concepts of sexism, bias and sexist ideology to understand the idea of the deep seated assumptions about the roles of men and women. The thesis concludes with some feminist theories and their studies of differential treatment as well as the assertion that feminism is incongruent with the strict confines of the law. It also reviews the various definitions and interpretations of equality. (Abstract shortened by UMI.)
Keywords: Law.